The Impact of Al-Shabr-Based Reframing Techniques on The Self-Esteem of Workplace-Bullying Victims - Anna Bella Diaz; Suci Nugraha; Anna Rozana (International Journal of Emerging Issues in Islamic Studies, 2024)
Bullying occurs not only among children but also among adults, especially in the workplace. Rejection, negative treatment, and a lack of appreciation in the work environment can affect self-esteem. It is crucial to enhance self-esteem in the context of work because work takes up a significant portion of an individual’s life and can impact their well-being. The application of Al-Shabr (commonly known as patience) with reframing techniques, focusing on resilience, perseverance, and steadfastness, aims to build confidence and optimism, develop resilience in facing challenges, and make efforts to overcome issues by setting new goals. This study, conducted on three workers experiencing workplace bullying and the resulting low self-esteem, used a one-group pre-test post-test design and was analyzed using the Wilcoxon test. The statistical results indicate that there are differences in results after implementing Al-Shabr-based reframing techniques, but the effect is not significant in terms of increasing the self-esteem of workers who experience bullying. The increase in scores showed that Al-Shabr-based reframing techniques had an impact on improving the self-esteem of workers who experienced bullying. Al-Shabr-based reframing techniques are promising and easy to implement but need to be tested on a wider sample.